Causes of delayed diagnosis of posterior ankle impingement in the pediatric and adolescent population. (June 2021) - Kushare, Indranil; Ditzler, Matthew; Gomez, Jorge; Jadhav, Siddharth
Highlights: Posterior ankle impingement is well known in the adult orthopedic literature seen classically in ballet dancers and soccer players, the diagnosis is based on detailed history and clinical examination. Our study shows that this diagnosis can be missed or delayed in the young patient population since it can be seen in sports other than ballet and soccer. Clinical examination finding of posterior joint line tenderness was the most common finding and should be included in the exam of all patients presenting with ankle pain. Radiographic features of Os trigonum, Stieda process and soft tissue should be looked for and help to confirm the diagnosis. Posterior ankle impingement syndrome diagnosis can be delayed in young patients due to multiple causes which can involve history of sport involvement, clinical exam, associated findings and imaging. Abstract: Purpose: The purpose of this study was to identify and characterize various causes of delay in the diagnosis of posterior ankle impingement syndrome (PAIS) in pediatric patients. Methods: IRB approved prospective study of patients under 18 years who underwent arthroscopic surgery for the diagnosis of posterior ankle impingement after failed conservative treatment at a tertiary children's hospital. Radiographic findings were compared with an age-matched control group. Descriptive and inferential statistics were employed. Results: 47 patients (61 ankles), mean age 13 years, had an average 14 months delay in diagnosis of PAIS from the initial presentation. 33 (70%) patients had seen multiple medical providers and given other diagnoses. 9 (19%) patients participated in ballet or soccer, and 16 (34%) patients had unrelated associated foot and ankle diagnoses. 25 (41%) of 61 ankles did not have pain on forced plantar flexion; all 61(100%) ankles had tenderness to palpation over the posterior ankle joint line. Radiographs were reported to be normal in 37/52 (71%) ankles, while MRI report did not mention the diagnosis in 20/41 (49%) studies. There was a significant difference in the MRI findings in the patient population when compared to the control group. Indication for surgery was failed conservative treatment. All 61 ankles had posterior ankle impingement pathology confirmed visually during arthroscopy. At average 15 months follow-up, there was significant improvement pre- to post-operatively ( p < 0.001) for both pain VAS (6.9–0.9) and AOFAS ankle-hindfoot scores (65–94). Conclusion: Multiple clinical and imaging factors can lead to delayed diagnosis of posterior ankle impingement. An increased awareness about the features of PAIS is needed amongst medical providers involved in treating young patients.